2015
DOI: 10.1073/pnas.1507159112
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient nonprecious metal catalyst prepared with metal–organic framework in a continuous carbon nanofibrous network

Abstract: Fuel cell vehicles, the only all-electric technology with a demonstrated >300 miles per fill travel range, use Pt as the electrode catalyst. The high price of Pt creates a major cost barrier for large-scale implementation of polymer electrolyte membrane fuel cells. Nonprecious metal catalysts (NPMCs) represent attractive low-cost alternatives. However, a significantly lower turnover frequency at the individual catalytic site renders the traditional carbon-supported NPMCs inadequate in reaching the desired perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
275
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 374 publications
(292 citation statements)
references
References 34 publications
11
275
1
4
Order By: Relevance
“…[5,6] The initial performances of FeNC based PEMFCs are superior to other NPMCs and even comparable with the commercial Pt/C(20%) nowadays. [7][8][9][10][11] Nonetheless, highly active FeNC catalysts usually suffer a quick current decay in acidic PEMFCs under a harsh operating condition, e.g., a constant voltage of 0.5 V with H 2 /O 2 . [12] It has been shown that MNC with highly graphitized carbon as catalyst supports, can exhibit decent fuel cell stabilities.…”
mentioning
confidence: 99%
“…[5,6] The initial performances of FeNC based PEMFCs are superior to other NPMCs and even comparable with the commercial Pt/C(20%) nowadays. [7][8][9][10][11] Nonetheless, highly active FeNC catalysts usually suffer a quick current decay in acidic PEMFCs under a harsh operating condition, e.g., a constant voltage of 0.5 V with H 2 /O 2 . [12] It has been shown that MNC with highly graphitized carbon as catalyst supports, can exhibit decent fuel cell stabilities.…”
mentioning
confidence: 99%
“…The maximum power density values of ~0.87 and 0.94 W cm -2 of as-prepared Fe-N-C catalyst, obtained at p O2 of 1.0 and 2.0 bar, respectively, were the highest ever achieved with PGM-free ORR catalysts operating on oxygen. 7 Under H 2 -air condition, the current density recorded in the kinetic range (> 0.75 V) of cathode operation, decreased with the increased thickness of catalyst-layer, illustrating the importance of catalyst-layer thickness on mass transport properties.…”
Section: -2mentioning
confidence: 89%
“…One is to tune pore distribution using framework substrates, and the other is to tune surface wettability using hydrophobic additives. [162]. c Tafel plot for the kinetic activity of Fe/N/CF obtained from a single fuel cell test [162].…”
Section: Mass Transportationmentioning
confidence: 99%
“…[162]. c Tafel plot for the kinetic activity of Fe/N/CF obtained from a single fuel cell test [162]. d Illustration of hydrophobic dimethyl silicon oil (DMS) just partially penetrating into the micropores with masstransport channels open, forming a robust triple-phase interface in micropores [163].…”
Section: Mass Transportationmentioning
confidence: 99%
See 1 more Smart Citation